Commanding with Politeness: English Lecturers' Directives at Institut Prima Bangsa - Rosalina, Utami (Sinergi International Journal of Education, 2024)
In the context of communication, the role of politeness in fostering positive interaction between interlocutors and their conversation partners cannot be overstated. This research addresses the existing gap in understanding of politeness strategies across different regions in Indonesia, with a particular focus on the strategies employed by an English lecturer at Institut Prima Bangsa Cirebon. The objective of this study is to identify the positive politeness strategies employed by the lecturer through a qualitative, phenomenological approach with data collected through observation. The findings indicate that the lecturer predominantly utilises directive speech acts, including commands, requests, and suggestions, during classroom interactions. The results identify seven key positive politeness strategies in the lecturer's directive speech acts, as follows: (1) Using Affectionate Greetings, (2) Involving Interlocutors and Hearers in activities, (3) Employing Subtle Request Markers, (4) Incorporating Humor, (5) Including Elements of Praise, (6) Considering the Wishes of the Speech Partner, and (7) Seeking Agreement These strategies are not only essential for the maintenance of a respectful and inclusive learning environment but also for enhanced student engagement. By employing these politeness techniques, the lecturer ensures that students feel valued and motivated to participate without feeling pressured or uncomfortable. This study contributes to the broader understanding of the function of politeness in the context of language learning and teaching, with particular reference to the diverse cultural landscape of Indonesia.